1994
DOI: 10.7164/antibiotics.47.1234
|View full text |Cite
|
Sign up to set email alerts
|

Structures of new 18-membered macrolides FD-891 and FD-892.

Abstract: Structures of FD-891 and FD-892 were determined by extensive NMRspectral analysis as shown in Fig. 1. They belong to such 18-memberedmacrolides as concanamycins and virustomycin.In the course of our screening program for low molecular substances inducing morphological changes of HL-60, new 18-membered macrolides FD-891 and FD-892 were discovered in the fermentation broth of Streptomyce graminofaciens A-88901}. They belong to such 18-membered antibiotics as concanamycins2'3) and virustomycin4'5). Their biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 13 publications
2
11
0
Order By: Relevance
“…1), which was isolated as a cytocidal compound for in vitro tumor cell lines (Seki-Asano et al 1994a, 1994bEguchi et al 2002Eguchi et al , 2004. A comparison of the retention time and UV spectrum in ODS-HPLC and of the 1 H-NMR spectrum of the phytotoxin with those of an authentic sample confirmed that the phytotoxin was FD-891.…”
Section: Isolation and Identification Of Phytotoxin Produced By Russementioning
confidence: 72%
“…1), which was isolated as a cytocidal compound for in vitro tumor cell lines (Seki-Asano et al 1994a, 1994bEguchi et al 2002Eguchi et al , 2004. A comparison of the retention time and UV spectrum in ODS-HPLC and of the 1 H-NMR spectrum of the phytotoxin with those of an authentic sample confirmed that the phytotoxin was FD-891.…”
Section: Isolation and Identification Of Phytotoxin Produced By Russementioning
confidence: 72%
“…[4] Macrolide FD-891, structurally related to the concanamycins even though it lacks a hemiketal moiety, was isolated in 1994 by a Japanese group from the fermentation broth of S. graminofaciens A-8890. [5] It shows cytotoxic activity against several tumour cell lines and, in addition, has been found to potently prevent both perforin-and Fasl-dependent CTlmediated killing pathways. In contrast to the structurally related concanamycin A, however, it is unable to inhibit vaAbstract: A total, stereoselective synthesis of the naturally occurring, cytotoxic macrolide FD-891 and of its nonnatural (Z)-C12 isomer is described.…”
Section: Introductionmentioning
confidence: 99%
“…The same PCR also afforded a probable concanamycin PKS gene (77 % identity to ConE), [36] which was anticipated to be amplified because this strain reportedly produces concanamycin. [37] Three other KS genes were also amplified, indicating that this strain has the potential to produce unidentified polyketides.…”
Section: Discussionmentioning
confidence: 99%